The impact of saw mark direction on the fracture strength of thin (120 µm) monocrystalline silicon wafers for photovoltaic cells. (30th July 2018) - Sekhar, Halubai; Fukuda, Tetsuo; Tanahashi, Katsuto; Shirasawa, Katsuhiko; Takato, Hidetaka; Ohkubo, Kazuya; Ono, Hiromichi; Sampei, Yoshiyuki; Kobayashi, Tsubasa
Abstract: Using a multi-diamond-wire saw, we cut monocrystalline silicon bricks into thin (120 µm) wafers, on which we observed saw marks and elongated pits with surface cracks. To address the fracture issues, we performed three-line bending tests with the load applied in the parallel and perpendicular direction to the saw mark direction. Under parallel loading, pits and accompanying cracks resulted in lower fracture strength than under perpendicular loading and the wafers were clearly separated into two groups: lower-strength wafers from the fresh-wire side and higher-strength wafers from the worn-wire side. Under perpendicular loading, the pits and surface cracks had less effect, resulting in higher strength. Using Raman spectroscopy, we confirmed that the wafers from the fresh-wire side had a higher fraction of slicing damage on the surface and subsurface region than those from the worn-wire side. This damage resulted in lower-strength wafers in the parallel loading test.